The philosophy and principles of welding design - Jubb, J. E. M. (College of Aeronautics, 1967)
The welding designer requires a philosophy for his design responsibilities and a thorough understanding of the basic principles in the subjects covering his responsibilities. The education of the welding designer must provide a spectrum of studies which will define these responsibilities and which will help him to understand and apply the science and technology relevant to his work.